Synthesis of the TiO2/g-C3N4 photocatalyst and its photocatalytic performance for selective oxidation of alcohols - Shuangyan Meng; Bin Liu; Minglin Xie; Chaoxin Yun; Jin Qiang; Kaizhou He; Zhiwang Yang; Xiangqian Wang (Química Nova)
A composite photocatalyst, xTCN (xOTiO2/g-C3N4, where x represents the added quantity of graphite carbon nitride (g-C3N4)), was synthesized using a straightforward one-step hydrothermal method with H2O2 as an oxidant. The H2O2 incorporation into the xTCN composite facilitated the enrichment of oxygen (O) in titanium dioxide (TiO2). This synthesis process effectively reduced the bandgap energy, minimizing the recombination of photogenerated carriers. Concurrently, an O atom was integrated into the g-C3N4 molecule, which altered its bandgap structure and enhanced the photogenerated electron-hole separation efficiency. The dual modification effect was observed when 0.9TCN was used as the catalyst, which converted 77% of benzalcohol with a selectivity exceeding 99%. Additionally, five cycles of reuse only slightly decreased the benzalcohol conversion (by 16%) and selectivity (by 9%), indicating good reusability of the xTCN photocatalyst. The xTCN photocatalyst had an unchanged molecular structure before and after the photocatalytic reaction, demonstrating its superior light stability. The potential photocatalytic reaction mechanism was explored through an active species capture experiment and a Mott-Schottky (M-S) curve test. The results of these studies suggested that •O2- and •OH were the primary reactive species in the photocatalytic reaction.